The Prevalence and Control of Type 2 Diabetes Mellitus in Residents of a Rural Town, Shandong Province, China - Wei M (Dove Medical Press, 2021)
Maoti Wei,1,* Li Dong,2,* Fenghua Wang,1 Kai Cui,3 Delong Ma,2 Ning Yang,4 Yuming Li4 1Center of Clinical Epidemiology, TEDA International Cardiovascular Hospital, Tianjin, People’s Republic of China; 2Department of Pediatrics, Center Hospital of Beikuo Town, Rizhao City, Shandong Province, People’s Republic of China; 3Department of Disease Prevention and Control, Hospital of Gaoxing Town, Rizhao City, Shandong Province, People’s Republic of China; 4Department of Hypertension, TEDA International Cardiovascular Hospital, Tianjin, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ning Yang; Yuming Li Email yangningzxdl@sina.com; cardiolab@live.comObjective: To understand the prevalence and control of type 2 diabetes mellitus (T2DM) in a rural area, a cross-sectional study was carried out.Methods: Blood glucose was determined in residents over 60 years during the National Basic Public Health Service project carrying on in a rural town of Shandong province. Combined with detail information of diabetic history, the prevalence rate of this disease was calculated with a cutoff of more than 7.0 mmol/L of fasting plasma glucose (FPG). Furthermore, according to FPG levels, the control rate of diabetes was evaluated. Basic information and clinical laboratory tests were analyzed with proper methods for univariate analysis. Multivariable logistic analysis was used to explore multiple variables associated with the control effect of T2DM.Results: The prevalence rate of T2DM was 13.5% (95% CI 12.4%∼ 14.7%) without age difference in residents over 60-year old (X2= 1.078, P = 0.898). And the rate was higher in the female (16.1%, 95% CI 14.4%∼ 17.8%) than that in the male (11.3%, 95% CI 9.7%∼ 12.9%). The control rate of diabetes was 44.5% (95% CI 39.4– 49.6%, cutoff < 6.1 mmol/L for FPG) and 59.6% (95% CI 54.5– 64.6%, cutoff < 7.0 mmol/L for FPG), respectively. Most T2DM residents had balance foods, and a high proportion of drugs or insulin were used; however, the proportion of keeping exercise and modifying behaviors was low. Nearly 80% of the diabetic individuals used at least one drug or insulin. However, the more drugs or insulin used, the higher the FPG level was.Conclusion: A relative high level of T2DM prevailed in the rural area under fast economy-transforming. T2DM was controlled poor and measures should be further optimized to achieve ideal effect, especially for the use of anti-diabetic drugs.Keywords: rural area, type 2 diabetes mellitus, the control of diabetes